Conceptual basis for creating the electronic service "Evaluation of the efficiency of the class teacher" - Sergey I. Aksenov; Anna A. Loshchilova; Ol’ga A. Katushenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper reveals and substantiates the conceptual foundations of an electronic service for evaluating the effectiveness of a class teacher, the relevance of which is due to the strategic priorities of modern education, the goals and objectives of the development of the state and society. The concept of an electronic service implements the key provisions of the author's methodology for evaluating the effectiveness of the class teacher, which provides the ability to design an assessment trajectory depending on the requests and needs of the class teacher and the administration of the educational organization. Theoretical provisions, approaches and principles for the development of an electronic service are determined, the purpose, functionality, roles, content, evaluation procedure, form and structure of the results presentation are presented. The principles of design, security requirements, as well as the possibilities and prospects for using the electronic service in the system of general and additional professional education are disclosed.